N. G. Сhernyshevskiy about insolvency of principle - Кривуц, Юрий Николаевич (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
Negative attitude of N. G. Chernyshevskogo is expounded to toward cardinal to position of doctrine of non-interference of the state in economic life. Especially it is unacceptable in krepostnicheskoy Russia, to the country by a peasant, began to be agricultural with not enough the developed mining industry at practically complete absence of processing industries.